Species composition and vegetation structure in Pakuli area, Lore Lindu National Park, Central Sulawesi - PURWANINGSIH PURWANINGSIH; RAZALI YUSUF (Biodiversitas Journal of Biological Diversity, 2005)
Forest ecological studies on some different altitude in Lore Lindu National Park, Central Sulawesi have been carried out with quadrate method. The plots were in altitude 500, 750 and 1000 m asl each 0.3 ha. This study would be covered on species composition, vegetation structure and potential plant species which used by locally people. The result from three plots recorded the totally species number as ± 85 species, consist of 64 genera and 38 families. The common species in three plots were Dracontomelon da’o, Aglaia odoratissima, Aglaia tomentosa, Palaquium obovatum, Planchonella nitida, and Pterospermum celebicum. Species regeneration in this location showed that sapling recorded 93 species consists of 74 genera and 46 families. The common species of sapling were Mallotus laevigatus, Antiaris toxicaria, Celtis philippensis, Macaranga hispida, Dendrocnide stimulans, Aglaia tomentosa, and Syzygium policephalloides. The forest structure could be seen from diameter and height stem classes, where commonly small trees but there have been still some big tree with diameter > 100 cm and height 50 m tall.© 2005 Jurusan Biologi FMIPA UNS SurakartaKeywords: species composition, vegetation structure, altitude, Lore Lindu National Park, Central Sulawesi